Durability and Lifecycle Requirements of Encapsulation Materials for Wireless Power Transfer Systems in Electric Road Applications - Jordan, Sophia; Kneidl, Maximilian; Weigelt, Michael; Masuch, Michael; Franke, Jörg; Risch, Florian (2025 IEEE Wireless Power Technology Conference and Expo, WPTCE 2025 - Proceedings, 2025)
Wireless Power Transfer (WPT) systems are an innovative technology for sustainable charging solutions in modern transportation, particularly within Electric Road Systems (ERS). Encapsulation materials play a critical role in ensuring the performance and reliability of these WPT systems. These materials must meet a range of demanding requirements throughout their lifecycle, from processing and installation to operation and recycling. This contribution examines the comprehensive lifecycle requirements for encapsulation materials in WPT systems, focusing on their mechanical, thermal, electrical, and environmental performance under real-world conditions. A systematic analysis identifies key challenges during processing, storage, transport, and integration into road structures, as well as during prolonged operation in varying environmental conditions. Practical experiments validate the performance of encapsulation materials under simulated aging conditions, offering valuable insights into their durability. The findings provide a framework for optimizing material selection and design to enhance the reliability and sustainability of WPT systems in ERS applications. Results are expected to support the implementation of robust and efficient wireless power transmission solutions for sustainable transportation systems.
CRIS-Team Scopus Importer:2025-08-01
Keywords: E-Road Infrastructure; Encapsulation Materials; Manufacturing; Thermal Aging; Wireless Power Transfer